Experience of «USPU» in Organization of School and University Partnerships in Training Teachers (Basic Professional Educational Program «Teacher of Primary General Education») - Voronina L.V.; Byvsheva M.V. (Психолого-педагогические исследования)
The article presents the experience of participation of the Ural State Pedagogical University in the project «Implementation of the Competence Approach in the Development and Approbation of the Main Professional Educational Programs of Higher Education in the EGSD «Education and Pedagogical Sciences (Bachelor's, Master's and Postgraduate Education, «Primary General Education Teacher» profile)». The organization of students' practice at the faculty of pedagogy and methods of primary education is disclosed, the theoretical positions and features of the pilot project «Modernization of the practice of future teachers in conditions of continuing education in higher education» are described. The requirements for the selection of general education organizations as network partners have been singled out. The forms of interaction of all participants of the practice, positively evaluated by students, teachers-instructors, and methodologists of the university are revealed. The authors note that one of the important moments in the organization of the school-university partnership is the purposeful preparation and development of the professional skills of mentor teachers to accompany students in the practice. The main tasks of the School of Mentors are listed in the article.